Time Quilt: Scaling up Zoomable Photo Browsers for Large, Unstructured Photo Collections - Huynh, David F.; Drucker, Steven; Baudisch, Patrick; Wong, Curtis (Conference on Human Factors in Computing Systems, 2005)
In the absence of manual organization of large digital photo collections, the photos’ visual content and creation dates can help support time-based visual search tasks. Current zoomable photo browsers are designed to support visual searches by maximizing screenspace usage. However, their space-filling layouts fail to convey temporal order effectively. We propose a novel layout called time quilt that trades off screenspace usage for better presentation of temporal order. In an experimental comparison of space-filling, linear timeline, and time quilt layouts, participants carried out the task of finding photos in their personal photo collections averaging 4,000 items. They performed 45% faster on time quilt. Furthermore, while current zoomable photo browsers are designed for visual searches, this support does not scale to thousands of photos: individual thumbnails become less informative as they grow smaller. We found a subjective preference for the use of representative photos to provide an overview for visual searches in place of the diminishing thumbnails.